Preserving a History of Digital Mapmaking: Inside the Geospatial Software and File Formats Documentation Web Archive (The Signal, 2025)
The goal of the Geospatial Software and File Formats Documentation Web Archive is primarily to ensure the long-term preservation of web materials which relate to GIS software and spatial data file formats. Gone are the days of getting software on a CD, accompanied by a thick booklet of documentation and instruction. Geospatial software companies and organizations now simply publish their documentation online and often only keep documentation available for the most recent version of their software. Given that one of the Geography & Map Division’s goals is to document the evolution of computer cartography and geographic information systems, it is part of our mission to capture how this geospatial software is changing over time.
United States of America